KH AHMAD SANUSI'S CONTRIBUTION TO ISLAMIC LITERATURE IN THE ARCHIPELAGO (A STUDY OF FORGOTTEN MANUSCRIPTS AND HISTORICAL DOCUMENTS) - Hamid, Abdul; Oktapiani, Marliza; Uyuni, Badrah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
This research examines the intellectual contribution of KH Ahmad Sanusi (1888–1950) in Islamic literature of the archipelago, which has received limited academic attention. Many of his manuscripts and historical documents remain forgotten or lost, weakening the continuity of local Islamic intellectual traditions. The study aims to uncover and analyze Sanusi’s surviving works, review their content and context, and situate his role in the historiography of Islam in the archipelago. Employing a literature-based method with Hans-Georg Gadamer’s hermeneutic approach, the research proceeds through the identification of problems, literature study, data collection, classification, content analysis, and conclusions. Data are drawn from Sanusi’s original works in tafsir, fiqh, Sufism, politics, and education, along with relevant secondary sources. Findings show that Sanusi used his writings as scientific contributions as well as instruments of da’wah, education, and intellectual resistance against colonialism. The study concludes that his legacy significantly shaped Islamic literary traditions, and its preservation is crucial to strengthening Islamic identity in Indonesia.